Effectiveness of Implementation of Office Spatial Principles in the Education and Culture Office of Pangkajene Regency and Islands - Haedar Akib; Andi Ditha Arianasari; Sitti Hardiyanti Arhas (Journal of Public Policy and Local Government (JPPLG), 2024)
Spatial planning has an important role in improving the effectiveness of employee work, so that the process of employee work flow can run smoothly and well, an effective office space arrangement is needed. This study aims to find out how the application of office spatial principles in the Education and Culture Office of Pangkajene Regency and Islands and what are the supporting and inhibiting factors of office layout in the Education and Culture Office of Pangkajene Regency and Islands. The type of research used was qualitative descriptive and data collection techniques, namely observation, interviews and documentation with five informants, namely employees of the Education and Culture Office. The results showed that the indicators used were effective. The intended indicator is that the shortest distance principle is quite effective due to the placement of facilities, only a few rooms still need to be fixed or arranged properly. The principle of the work series is classified as effective because the placement of office equipment and each flow of workers has met the requirements of Standard Operating Procedures (SOP), where all work activities start from the field of integrated services, so that work can be done effectively and efficiently. The principle of using all parts of the room is quite effective because the existing room has been fully used according to the field and tree tasks and their functions. The principle of changing the composition of the workplace is classified as ineffective because there are informants stating that there is no need for changes in the arrangement because the available space is sufficient. The principle of integration of activities is classified as effective because  spatial planning and equipment have unified each division. The principle of security and job satisfaction is classified as effective because it has been fulfilled in terms of spatial planning and office equipment is good at making employees comfortable, safe, and has met employee satisfaction.